2011
DOI: 10.2139/ssrn.1926475
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on Inflation and Unemployment in the Long Run

Abstract: We examine the relationship between inflation and unemployment in the long run, using quarterly US data from 1952 to 2010. Using a band-pass filter approach, we find strong evidence that a positive relationship exists, where inflation leads unemployment by some 3 to 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Also, the positive inflation rate (though not significant) is against the theoretical proposition of the Phillips Curve Hypothesis, which states that unemployment and inflation rates are negatively related. This outcome seems rather not peculiar to us, as it is already on record that most developing countries, especially those of the African continent, suffer rising unemployment rates in the face of the high inflation rate, a phenomenon known as stagflation (Haug & King, 2011). Thus, this finding stands in contrast to that of Ebaidalla (2014), which concluded that the Phillips Curve Hypothesis is valid for the SSA countries.…”
Section: Resultsmentioning
confidence: 93%
“…Also, the positive inflation rate (though not significant) is against the theoretical proposition of the Phillips Curve Hypothesis, which states that unemployment and inflation rates are negatively related. This outcome seems rather not peculiar to us, as it is already on record that most developing countries, especially those of the African continent, suffer rising unemployment rates in the face of the high inflation rate, a phenomenon known as stagflation (Haug & King, 2011). Thus, this finding stands in contrast to that of Ebaidalla (2014), which concluded that the Phillips Curve Hypothesis is valid for the SSA countries.…”
Section: Resultsmentioning
confidence: 93%
“…While, the study by Pallis (2006) for 10 EU countries indicated that application of common policies across economies may be questionable because of the different effect of these policies on inflation and unemployment. The study by Haug and King (2011) on US affirmed the proposition of Philips curve of a negative relationship between unemployment and inflation. On the hand, Umoru and Anyiwe (2013) using a vector error correction approach to establish the dynamic relationship between inflation and unemployment in Nigeria found it to be positive.…”
Section: Empirical Reviewmentioning
confidence: 76%
“…Thus, based on the Phillip curve, it is expected that a negative relationship should exist between inflation rate and unemployment rate. The study of Furuoka and Munir (2014), Li and Liu (2012), Vermeulen (2015) and Yelwa, David, and Awe (2015), Eita and Ashipala (2010), Aminu and Anono (2012), Afzal and Awais (2012) and Haug and King (2011) were in support of the Phillip curve.…”
Section: Inflation Ratementioning
confidence: 89%